Voltamperometric discrimination of urea and melamine adulterated skimmed milk powder - Hilding-Ohlsson, A. (2012)
Nitrogen compounds like urea and melamine are known to be commonly used for milk adulteration resulting in undesired intoxication; a well-known example is the Chinese episode occurred in 2008. The development of a rapid, reliable and economic test is of relevance in order to improve adulterated milk identification. Cyclic voltammetry studies using an Au working electrode were performed on adulterated and non-adulterated milk samples from different independent manufacturers. Voltammetric data and their first derivative were subjected to functional principal component analysis (f-PCA) and correctly classified by the KNN classifier. The adulterated and non-adulterated milk samples showed significant differences. Best results of prediction were obtained with first derivative data. Detection limits in milk samples adulterated with 1% of its total nitrogen derived from melamine or urea were as low as 85.0 mg·L-1 and 121.4 mg·L-1, respectively. We present this method as a fast and robust screening method for milk adulteration analysis and prevention of food intoxication. © 2012 by the authors; licensee MDPI, Basel, Switzerland.